A Simple Approach to Testing the Potency of Government Purchases to Stimulate Aggregate Demand - Hatzinikolaou, Dimitris (Journal of Reviews on Global Economics, 2013)
Abstract: The paper proposes a new approach to testing the potency of government purchases to stimulate the economy by testing a set of conditions implied by the Ricardian Equivalence (RE) proposition that a typical household incorporates the government’s budget constraint into its own. These conditions are as follows: (1) private consumption, income, and government purchases form a â€œlevels relationshipâ€; and (2) considering consumption as the dependent variable, the coefficients of income and of government purchases are 1 and -1. The last restriction is also implied by the hypothesis that consumption and government purchases are perfect substitutes, however, so the proposed approach cannot distinguish between the perfect substitutability and the RE hypotheses. This restriction is thus referred to in the paper as the hypothesis of direct or ex ante full crowding out. If it holds, then the multiplier of government purchases is zero. Using US quarterly data, 1947.1-2012.1, the results suggest that a â€œlevels relationshipâ€ exists and that the coefficient of government purchases is about -0.4 and significantly below -1, thus leading to the conclusion that government purchases stimulate aggregate demand and output.